The role of inflammatory system genes in individual differences in nonverbal intelligence - R. F. Enikeeva; A. V. Kazantseva; Yu. D. Davydova; R. N. Mustafin; Z. R. Takhirova; S. B. Malykh; Y. V. Kovas; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции)
Nonverbal intelligence represents one of the components of brain cognitive functions, which uses visual images and nonverbal approaches for solving required tasks. Interaction between the nervous and immune systems plays a specif ic role in individual differences in brain cognitive functions. Therefore, the genes encoding pro- and antiinf lammatory cytokines are prospective candidate genes in the study of nonverbal intelligence. Within the framework of the present study, we conducted the association analysis of six SNPs in the genes that encode proteins involved in inf lammatory response regulation in the central nervous system (CRP rs3093077, IL1А rs1800587, IL1B rs16944, TNF/ LTA rs1041981, rs1800629, and P2RX7 rs2230912), with nonverbal intelligence in mentally healthy young adults aged 18– 25 years without cognitive decline with inclusion of sex, ethnicity and the presence of the “risky” APOE ε4 allele as covariates. Considering an important role of environmental factors in the development of brain cognitive functions in general and nonverbal intelligence in particular, we conducted an analysis of gene-by-environment (G × E) interactions. As a result of a statistical analysis, rs1041981 and rs1800629 in the tumor necrosis factor gene (TNF) were shown to be associated with a phenotypic variance in nonverbal intelligence at the haplotype level (for АА-haplotype: βST = 1.19; p = 0.033; pperm = 0.047) in carriers of the “risky” APOE ε4 allele. Gene-by-environment interaction models, which determined interindividual differences in nonverbal intelligence, have been constructed: sibship size (number of children in a family) and smoking demonstrated a modulating effect on association of the TNF/LTA (rs1041981) (β = 2.08; βST = 0.16; p = 0.001) and P2RX7 (rs2230912) (β = –1.70; βST = –0.10; p = 0.022) gene polymorphisms with nonverbal intelligence. The data obtained indicate that the effect of TNF/LTA on the development of cognitive functions is evident only in the presence of the “unfavorable” APOE ε4 variant and/or certain environmental conditions.